Optimization of a novel peptide ligand targeting human carbonic anhydrase IX - Rana, Shoaib; Nissen, Felix; Marr, Annabell; Markert, Annette; Altmann, Annette; Mier, Walter; Debus, Jürgen; Haberkorn, Uwe; Askoxylakis, Vasileios (PLOS ONE, 2012)
Background Carbonic anhydrase IX (CA IX) is a hypoxia-regulated transmembrane protein over-expressed in various types of human cancer. Recently, a new peptide with affinity for human carbonic anhydrase IX (CaIX-P1) was identified using the phage display technology. Aim of the present study is to characterize the binding site in the sequence of CaIX-P1, in order to optimize the binding and metabolic properties and use it for targeting purposes. Methodology/Principal Findings Various fragments of CaIX-P1 were synthesized on solid support using Fmoc chemistry. Alanine scanning was performed for identification of the amino acids crucial for target binding. Derivatives with increased binding affinity were radiolabeled and in vitro studies were carried out on the CA IX positive human renal cell carcinoma cell line SKRC 52 and the CA IX negative human pancreatic carcinoma cell line BxPC3. Metabolic stability was investigated in cell culture medium and human serum. Organ distribution and planar scintigraphy studies were performed in Balb/c nu/nu mice carrying subcutaneously transplanted SKRC 52 tumors. The results of our studies clearly identified amino acids that are important for target binding. Among various fragments and derivatives the ligand CaIX-P1-4-10 (NHVPLSPy) was found to possess increased binding potential in SKRC 52 cells, whereas no binding capacity for BxPC3 cells was observed. Binding of radiolabeled CaIX-P1-4-10 on CA IX positive cells could be inhibited by both the unlabeled and the native CaIX-P1 peptide but not by control peptides. Stability experiments indicated the degradation site in the sequence of CaIX-P1-4-10. Biodistribution studies showed a higher in vivo accumulation in the tumor than in most healthy tissues. Conclusions Our data reveal modifications in the sequence of the CA IX affine ligand CaIX-P1 that might be favorable for improvement of target affinity and metabolic stability, which are necessary prior to the use of the ligand in clinical approaches.
Gesehen am 21.11.2018